2018
DOI: 10.1111/ecc.12894
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of living with head and neck lymphoedema and the impacts to swallowing, voice and speech function

Abstract: Head and neck lymphoedema (HNL) is common following head and neck cancer (HNC) treatment, and may contribute to numerous physical, functional and psychological symptoms. However, its impact on swallowing, voice and speech is less well understood. The aim of this study was to use interpretive description to explore patient perceptions relating to the impact of HNL on swallowing, voice and speech. Twelve participants, >3 months post HNC treatment and experiencing some form of HNL, participated in individual, sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…The majority of patients treated for HNC will likely undergo multiple transnasal laryngoscopies for ongoing cancer surveillance, or a fiberoptic endoscopic evaluation of swallowing (FEES) to examine swallow function; and these represent opportune moments to incorporate internal HNL screening. Previous research has also shown that patients with internal HNL often experience altered sensations within the head and neck region, such as a perceived change in the size of the pharyngeal lumen 22,34 . Increased attention to these patient‐reported symptoms may also allow clinicians to screen and diagnose internal HNL in a timelier manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of patients treated for HNC will likely undergo multiple transnasal laryngoscopies for ongoing cancer surveillance, or a fiberoptic endoscopic evaluation of swallowing (FEES) to examine swallow function; and these represent opportune moments to incorporate internal HNL screening. Previous research has also shown that patients with internal HNL often experience altered sensations within the head and neck region, such as a perceived change in the size of the pharyngeal lumen 22,34 . Increased attention to these patient‐reported symptoms may also allow clinicians to screen and diagnose internal HNL in a timelier manner.…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, lymphedema may ultimately progress and result in the development of fatty tissue deposits and further the development of fibrosis 5,9,35 . There is the potential for those affected patients to have significant symptom burden, 19‐22 which may ultimately have detrimental effects on quality of life. The widespread presence of chronic HNL in the current cohort reinforces the need for improving early screening and diagnostic processes, to better facilitate early intervention and in order to help to minimize, where possible the presence of HNL 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three qualitative studies have concluded that patients often perceive a link between the presence of HNL and swallowing function. [16][17][18] In one study, 18 11 of 12 patients felt that their HNL made it harder for them to swallow, and these patients spoke of having to modify their diets and use additional compensatory strategies during mealtimes. Patients also reported more difficulties with solid foods, rather than fluids.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 A number of qualitative studies have also shown that patients often perceive a link between their HNL and swallow function. [16][17][18] One study reported that 11 of 12 participants with long-term HNL felt that that their HNL had altered their swallow function in some way. 18 Participants described feelings of tightness and swelling within their pharynx that had various impacts on swallowing, including negative effects on bolus flow with solid foods.…”
Section: Introductionmentioning
confidence: 99%